Sistem Informasi RT/RW Sebagai Media Komunikasi Warga Berbasis Web - Widodo, Anita, Sugeng (SMATIKA, 2014)
Rukun tetangga/rukun warga (RT / RW) is an institution established through consultation with theÂ local community in order to provide services to citizens. RT / RW has an important role in maintaining andpreserving the values of a society that is based on mutual cooperation and kinship; facilitate theimplementation of the governments job in rural or urban and community development, as well as empowerall governmental organizations and businesses to improve the welfare of society. Therefore, the RT / RWshould provide a good service for the citizens that create a conducive society. Society needs a service at anytime, but the service can only be provided to the citizens during the afternoon or day off becauseadministrators RT / RW has personal interests. These problems can be overcome by building a web-basedinformation system that is capable of being a medium of communication between citizens and administratorsRT / RW.